Pengetahuan Gizi, Sikap dan Pola Makan dengan Profil Lipid Darah pada Pegawai Rumah Sakit Mata Cicendo Bandung - Sunarti, Sunarti (Lembaga Penerbitan Unversitas Esa Unggul, 2010)
AbstractOne of factors that led to the emergence of cardiovascular disease is a disorder of blood lipid, called dyslipidemia which has increasing level of total colesterol hypercolesterolemia), elevating levels of low density lipoprotein (LDL), decreasing levels of high density lipoprotein (HDL) and increasing levels of tryglycerides (hypertriglycerides). Food consumption pattern which were influenced by nutrition knowledge and attitude person could transform blood lipid profile. The aims of this study is to determine the relationship between nutrition knowledge, attitudes, food consumption pattern and blood lipid profile in employees at Cicendo Eye Hospital, Bandung. This study used cross-sectional design. The population of this study is hospital employees. The random sampling method used to get the sample (69 people). This study used Chi-square test and multiple logistic regression modelling test to analyze the data. The results showed that there is a significant relationship between knowledge and attitudes, attitudes and food consumption pattern. There is no relationship between knowledge, attitudes, food consumption pattern and profile of total cholesterol, LDL, and HDL. There is a significant relationship between knowledge, attitudes, food consumption pattern and triglyceride lipid profile. The dominant factors associate to blood lipid profile are the attitude and diet. Knowledge, attitudes, and food consumption pattern can be affect to blood lipid profile. There are another factors influence the blood lipid profile which are not investigated in this study.Keywords: nutrition knowledge, food consumption pattern, blood lipid profileAbstrakSalah satu faktor penyebab timbulnya penyakit kardiovaskuler adalah gangguan lipid darah yang disebut dengan dislipidemia berupa peningkatan kadar kolesterol total (hiperkolesterolemia), peningkatan kadar low density lipoprotein (LDL), penurunan kadar high density lipoprotein (HDL) dan kenaikan kadar trigliserida (hipertrigliserida). Penyebab perubahan profil lipid darah adalah pola makan yang dapat dipengaruhi oleh pengetahuan gizi dan sikap seseorang. Penelitian ini bertujuan mengetahui hubungan tingkat pengetahuan gizi, sikap dan pola makan dengan profil lipid darah Pegawai Rumah Sakit Mata Cicendo Bandung. Design penelitian cross-sectional dengan populasi pegawai RS. Mata Cicendo Bandung. Sampel yang diambil secara acak didapat 69 orang. Analisa yang digunakan uji chi-square dan pemodelan multiple logistic regression test . Terdapat hubungan bermakna antara pengetahuan dan sikap, sikap dan pola makan.Tidak terdapat hubungan bermakna antara pengetahuan, sikap dan pola makan dengan profil kolesterol total, LDL dan HDL. Terdapat hubungan bermakna antara pengetahuan, sikap dan pola makan dengan profil lipid trigliserida. Faktor paling dominan berhubungan dengan profil lipid darah pegawai Rumah Sakit Mata Cicendo Bandung adalah sikap dan pola makan. Pengetahuan, sikap, dan pola makan berpengaruh terhadap profil lipid darah, namun ada faktor-faktor lain yang berpengaruh yang tidak diteliti pada penelitian ini.Kata kunci: pengetahuan gizi, pola konsumsi makanan, profil lipid darah